Diseminasi Informasi Melalui Media Sosial Pada Badan Pusat Statistik Karawang - Syarif Firmansah; Sungkono Sungkono (OPTIMAL Jurnal Ekonomi dan Manajemen, 2023)
The study, entitled "Information Dissemination Through Social Media on the Indonesian Central Statistical Authority", aims to find out how the Karawang District Statistics Authority uses social media, especially Instagram. The data collection method in this study uses documentation from the Instagram media BPS Karawag. The method used is qualitative. As a result of this study, Instagram has been widely used by BPS Karawang as a media of statistical promotion at 53.8 percent, the media of general information at 30.7 percent, and statistical knowledge media and job information at 7.6 percent, respectively. The average number of interactions on the Instagram posts of the Center for Statistics of Karawang District is 50. Agriculture, Census, Indonesia, and 2023 are the main topics of information spread through activity posts.